Karakterisasi Blok Rem Kereta Api Berbahan Al-Sic Berdasarkan Komposisi Material - Kurniawan, Ipung; AP, Bayuseno (Majalah Ilmiah Gema Maritim, 2011)
Brake blocks is a vital component in the braking system of trains. Generally material brake blocks made ​​of cast iron. But the usage is still less effective than the weight and resistance to wear. Al-SiC composites with the variation of weight fraction of 5, 10 and 15% SiC is expected to address the problem as expected. Stir casting method was chosen for the process of formation of Metal Matrix Composites (MMC), which includes the characterization of microstructure and wear of materials. Wear and tear on the material tested by the method ogoshi at 2.12 kg load and a constant sliding speed 0.244 m/s for 60 seconds. Small value indicates the specific wear resistance of materials against wear is good.